Pengembangan Kemampuan Tour Guide Desa Warnasari Kecamatan Pengalengan Kabupaten Bandung - Alif Oktavia; Tine Ratna Poerwantika; Kunkunrat Kunkunrat; Rini Afriantari (Universitas Serang Raya, 2020)
The Warnasari Village Tourism Area is a place that offers the attraction of natural scenery and stretches of plantations. The Warnasari Village Tourism Area is projected by the Bandung Regency Culture and Tourism Office as one of the leading tourist destinations in South Bandung. The purpose of this activity is to improve the ability of the Tour Guide of Warnasari Village, Pengalengan District, Bandung Regency.Activities carried out for 3 months. Methods of using training. The target of the activity is Karang Taruna, the manager of the attractions of Warnasari Village, amounting to 30 people.The results of this activity have a positive impact with the implementation of tourist training activities so that there is an increase in the management of tourist objects and increased ability of the Tour Guide of Warnasari Village, Pengalengan District, Bandung Regency.